2008
DOI: 10.1248/bpb.31.2028
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Sanguisorbae Radix against Oxidative Stress-Induced Brain Damage: in Vitro and in Vivo

Abstract: Stroke is the third leading cause of death and an important factor that may affect morbidity and long-term disability. It has been suggested that ischemic stroke may result in the interruption and/or severe reduction of blood flow in cerebral arteries.1) The brain has an absolute dependence on the blood for its immediate supply of oxygen and energy substrates.2)The depletion of energy stores influenced by interruption of the cerebral blood flow can cause several acute metabolic disturbances, such as disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 58 publications
4
36
0
4
Order By: Relevance
“…# P \ 0.05 versus SAH ? Hepc group activation [25][26][27][28]. The results of this study also indicated that hepcidin-targeting siRNA treatment mitigates the brain damage in the rat model of SAH.…”
Section: Discussionsupporting
confidence: 57%
“…# P \ 0.05 versus SAH ? Hepc group activation [25][26][27][28]. The results of this study also indicated that hepcidin-targeting siRNA treatment mitigates the brain damage in the rat model of SAH.…”
Section: Discussionsupporting
confidence: 57%
“…Because exogenously administered H 2 O 2 is one of the most widely used methods to induce cytotoxicity [16][17][18] , we evaluated the neuroprotective effects of sinomenine during H 2 O 2 -induced injury in PC12 cells. Pretreatment with sinomenine significantly attenuated H 2 O 2 -induced PC12 cell death, in a dose-dependent manner, at a concentration range of 0.060 to 0.600 μg/mL of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Sanguisorba officinalis Linne (Rosaceae) is a traditional Chinese herbal plant, officially listed in the Chinese Pharmacopoeia, with multiple pharmacological functions, such as anti-infection, anti-inflammatory, antitumor, and neuroprotective effect (Cai et al, 2012;Lee et al, 2010;Nguyen et al, 2008;Yu et al, 2011). Although numerous activities of this plant have been reported and published so far, not many reports explicitly explain the mechanisms that underlie the immunomodulation and macrophage activation properties of S. officinalis.…”
Section: Introductionmentioning
confidence: 99%